Cellular and humoral immune response to exercise among gymnasts and untrained girls - Eliakim, A.; Wolach, B.; Kodesh, E.; Gavrieli, R.; Radnay, J.; Ben-Tovim, T.; Yarom, Y.; Falk, B. (International Journal of Sports Medicine, 1997)
Recent studies reported reduced immunity in athletes following exercise. Physical activity affects both cellular and humoral immune functions. Scant information exists on exercise-induced changes in the immune system among children. The purpose of the present study was to investigate the effect of aerobic exercise on several aspects of cellular and humoral functions among 10-12 year-old highly trained female gymnasts (n = 7) and untrained girls (n = 6). All girls were pre-pubertal. Venous blood samples were drawn before, immediately after and 24 h following 20 min of treadmill running (heart rate 170-180 beats.min-1). White blood cells' number rose significantly following exercise and remained elevated for 24 h. The increase in leukocyte number was due to an increase in granulocytes as well as an increase in lymphocytes and monocytes. While neutrophil count returned to basal values after 24 h, lymphocytes and monocytes number remained elevated 24 h following exercise. Exercise resulted in a significant elevation of T cell lymphocytes, T helpers, T suppressors and natural killer cells. All values returned to normal after 24 h. There were no changes in B cell lymphocytes following exercise. Exercise had no effect on serum IgA, IgM, IgE, IgG and sub-types of IgG (IgG1, IgG2, IgG3 and IgG4). No differences were observed between gymnasts and untrained girls. In summary, the exercise-induced changes in cellular and humoral immune functions among the girls were generally similar to those described in adults. Whether the transitory effects of exercise on the immune system are related to increased susceptibility to illness is still questionable.